The Attribute of the Energy of Fuel Briquette from Mangosteen Peel and Rubberwood - Markphan, Wattananarong; Suttara, Kiattichai; Nukeaw , Jutamast; Tiprung, Udom (Burapha Science Journal, 2026)
This research aims to study the attribute of the energy and an economic evaluation of fuel briquette from mangosteen peel and rubberwood which is the ratio 100:0 90:10 80:20 70:30 60:40 50:50 and 0:100 (% by weight)by giving the highest average heat equal to 7,361.55 cal/g, which is the ratio 80:20 by weight. The average carbon content of almost 96.67 %, the ratio of 100: 0 by weight. The average volatile substances 95.73 %, the ratio 60:40 by weight. The smallest average ash content Representing 10.68 %, which ratio 60:40 by weight and Average moisture content is minimal 50:50 ratio was 5.32 % by weight. An economic value analysis of briquette fuel production is analysis the cost per unit of production Which the least cost per 1 Kg of briquette fuel production is equal to 9.22 baht/Kg, which is the ratio 80:20 by weight.